Female Reproductive Decline Is Determined by Remaining Ovarian Reserve and Age - Wilkosz, Pawel; Greggains, Gareth D.; Tanbo, Tom G.; Fedorcsak, Peter (PLOS ONE, 2014)
The early decline and loss of female fertility in humans and other species represents an evolutionary paradox. Despite being born with a vast stock of oocytes, females encounter an exhaustion of ovarian reserve and sterility half way through their natural lives. Female reproductive ageing has been proposed to proceed as an ongoing decline in ovarian reserve, determined by remaining ovarian follicle number. However, despite extensive modelling, the respective contributions of intra-, inter-, and extra-ovarian signalling have not been fully characterised. It remains unclear whether reproductive ageing progresses simply as a pre-determined function of remaining ovarian follicles, or as an age-dependent process in humans. Here, we have analysed ovarian response to hormonal stimulation in women who have undergone surgical removal of a single ovary, in order to investigate the relative contributions of intra-, inter, and extra-ovarian signalling on reproductive ageing. Our data show that in unilaterally oophorectomised women, ovarian response to follicle stimulating hormone (FSH) declines beyond levels predicted by a total ovarian follicle pool model of reproductive ageing. Maintenance of ovarian function later in reproductive life, despite the removal of half of the total ovarian reserve, suggests a role for an extra-ovarian age-dependent regulation of reproductive decline. This highlights the need for further work to identify signalling factors that communicate age-related signals between the soma and the germline.